Indigenous people's experiences at the end of life. Issue 6 (15th June 2015) - Duggleby, Wendy; Kuchera, Samantha; MacLeod, Rod; Holyoke, Paul; Scott, Tracy; Holtslander, Lorraine; Letendre, Angeline; Moeke-Maxwell, Tess; Burhansstipanov, Linda; Chambers, Thane
ABSTRACT: Objective: The primary purpose of this metasynthesis study was to explore the end-of-life experiences of Indigenous peoples by synthesizing the findings of qualitative research. Method: Sandelowski and Barroso's methodology for synthesizing qualitative research was used and included (a) a comprehensive search, (b) appraising reports of qualitative studies, (c) classification of studies, and (d) synthesis of the findings. Research team members guided this process. This team was multidisciplinary and included Indigenous and non-Indigenous researchers from Canada, Australia, New Zealand, and the United States. Following a comprehensive search, 2255 studies were reviewed and assessed against five inclusion criteria: (a) studies on the experiences of Indigenous populations (all genders, 18 + years of age) at the end of life, (b) studies published in English from any country, (c) studies using qualitative and mixed-methods designs, and (d) studies published between 1993 and 2013. Results: Some 18 studies met the inclusion criteria, and their findings were synthesized. "Preparing the spirit" for transition to the next life was the overarching theme. "Preparing the spirit" occurred within the context of "where we come from." Processes involved in "preparing the spirit" were healing, connecting, and protecting; through these processes, "what I want at the end of life" was realized. Although not the focus of the metasynthesis, a significant finding was that the studies reviewed identified very clear barriers within healthcare systems and current healthcare provider practices to "preparing the spirit." Significance of results: The findings provide a beginning understanding of the end-of-life experiences of Indigenous peoples and a foundation for future research. More interpretive qualitative research is critical if palliative care services, the healthcare system, and healthcare providers are to reduce current barriers to "preparing the spirit" for the journey at the end of life.